Structural reforms in EMU and the role of monetary policy – a survey of the literature - Nadine Leiner-Killinger; Victor López Pérez; Roger Stiegert; Giovanni Vitale (European Central Bank (ECB), 2007)
The need for structural reforms in the euro area has often been advocated. These reforms would improve the welfare of euro area citizens and also, as a welcome side-effect, facilitate the conduct of monetary policy. Against this background, a particularly relevant question that can be posed is whether monetary policy should help implement structural reforms. The objective of this paper is to provide a review of the existing literature on structural reforms in Economic and Monetary Union (EMU) and to discuss the possible ways in which monetary policy could support the structural reform process. In the context of EMU, the main conclusions that emerge are that the monetary policy for the euro area is not the appropriate tool for mitigating the potential and uncertain short-term costs of reforms or for providing incentives for structural reforms at the national level. However, credible monetary policy aimed at price stability can improve the functioning of the supply side of the economy and contribute to an environment which is conducive to welfare-enhancing structural changes. In addition, the ECB's contribution to the implementation of structural reforms takes the form of analysis, assessment and communication.
Keywords: 330; Wirtschaftliche Anpassung; Geldpolitik; Eurozone; EU-Staaten